“Languages are not the barriers”: Learning together through multilingual cross-curricular poetry writing in the ESL classroom - Kalthoum, Eyad (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2024)
The evolving linguistic landscape in 21st century classrooms necessitates a re-evaluation of pedagogical approaches, exploring the potential of multilingual writing techniques within TESOL settings. This article draws on my self-study as a TESOL educator navigating contexts and shifting from an English-only approach in the classroom to an openness of language(s) approach (Ortega, 2019). Following Hamilton’s (2018) case study approach, I investigate the feasibility of implementing a multilingual pedagogy in an international school in Toronto and explore its influence on students, teachers, and the learning process across the domains of (CMLA) (Prasad & Lory, 2020). For this paper, I focus on data that highlight and reflect the impact of multilingual pedagogy on students, teachers, and the teaching/learning process. I performed a qualitative thematic analysis and found that multilingual pedagogies benefited students on many levels. I conclude with a personal reflection on both the affordances and challenges of implementing multilingual pedagogies.